Primary cutaneous non-Hodgkin lymphoma: results of a retrospective analysis in the light of the recent ILROG guidelines. Issue 5 (October 2018) - Pedretti, Sara; Urpis, Mauro; Leali, Carla; Borghetti, Paolo; Baushi, Liliana; Sala, Raffaella; Tucci, Alessandra; Greco, Diana; Pasinetti, Nadia; Triggiani, Luca; Rossi, Giuseppe; Calzavara-Pinton, Piergiacomo; et al.
Purpose: To analyze clinical outcome, local response, survival and toxicity in patients with primary cutaneous lymphoma (PCL) treated with radiotherapy. Methods: From 1995 to 2014, 112 patients were treated. B-cell lymphomas (CBCLs; n = 86) and T-cell lymphomas (CTCLs; n = 23) were analyzed separately. Clinical and therapeutic characteristics (age, sex, histology, primary treatment and radiotherapy modality) were related to response to treatment, survival and toxicity. Results: CBCLs were divided into 4 subgroups: marginal-zone lymphoma (n = 20), follicle center lymphoma (n = 32), diffuse large-cell lymphoma (DLBCL; n = 22) and DLBCL-leg type (n = 12). No significant correlation was found between doses and systemic treatments, extent of biopsy and number of lesions. DLBCL-leg type patients were older (p = 0.05), had disseminated disease (p = 0.034), and more frequently had local (p = 0.01) or systemic recurrence (p = 0.05). CTCLs were divided into 4 subgroups: α/β CTCL (n = 3), nasal type CTCL (n = 0), γ/δ CTCL (n = 10) and mycosis fungoides (n = 10). Longer disease-free survival was observed in patients obtaining complete remission (p<0.001). Conclusions: Radiotherapy is feasible, safe and effective for localized PCLs. The choice of dose is related to histological subgroups and the related prognoses. Survival results are very good also in relapsing disease. In advanced cutaneous lymphoma radiotherapy alone has mainly a role in symptom palliation.